(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
This research aims to know and investigate the benefits and possible negatives of the project Aula Link: School without borders, which is directed by Professor Hernán López, who has a degree in Social Sciences from the Marsella IED school, located in the Kennedy town. Which is based on an initiative that consists of connecting students through Skype with students, teachers and professionals anywhere in the world in order to learn history, geography, promote the experience of human rights, and in general to offer them an extensive experience of the world around them. The data collection instruments that were implemented to carry out this research were; conducting the interview and reviewing some sources of information that spoke about this educational project. Which allowed to have a basis for the foundation and justification of such research. It is important to emphasize the fruitful results that were obtained thanks to this data collection instrument, which allowed us to know a series of benefits that ICT generated by its use in Professor Hernán’s class. Aula Link: Escuela sin fronteras is a project with which you can exemplify the use and fruitful results that its use brings with it, Professor Hernán López has been with this project for more than five years, therefore, he has experience and foundation in its results .